SOME LESS KNOWN HERBAL REMEDIES AGAINST WOUNDS FROM JAMKHED TAHASIL AREAS IN AHMEDNAGAR DISTRICT (M.S.) INDIA - Punjaji*, Salave Ashok (Journal of Pharmaceutical Research and Opinion, 2014)
An extensive field surveys were arranged in Jamkhed tahasil areas to document ethno-medicinal uses of the native ethno-flora against wounds. The information was collected during the period from pre-monsoon of 2009 to the post-monsoon of 2011, from the local inhabitants through verbal interviews via informal ways. The paper focuses on the ethno-medicinal uses of 35 genera belonging to 24 families used against wounds formed due to certain reasons among the local inhabitants.